2013
DOI: 10.1186/1477-7819-11-141
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HSPA2 is correlated with poor prognosis in esophageal squamous cell carcinoma

Abstract: BackgroundHeat shock-related 70 kDa protein 2 (HSPA2) has been identified as a potential cancer-promoting protein expressed at abnormal levels in a subset of cancers. However, its important role in esophageal squamous cell carcinoma (ESCC) is hardly known by people. The purpose of this study is to assess HSPA2 expression and to explore its role in ESCC.MethodsThirty ESCC samples, paired adjacent non-cancerous tissues and normal esophageal tissues, were collected for HSPA2 detection by quantitative RT-PCR (qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…It has been shown that proliferation and development of esophageal epithelial cells are associated with the development of ESCC [36]. Moreover, ESCC-related gene modules are significantly enriched in epidermal cell differentiation, epithelial cell differentiation, epidermis development, and keratinocyte differentiation [37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that proliferation and development of esophageal epithelial cells are associated with the development of ESCC [36]. Moreover, ESCC-related gene modules are significantly enriched in epidermal cell differentiation, epithelial cell differentiation, epidermis development, and keratinocyte differentiation [37].…”
Section: Discussionmentioning
confidence: 99%
“…HCC patients generally have poor performance in veyear OS [1]. HSP70 was reported to be highly expressed in a number of cancer types, like esophagus, bladder, prostate, lung and colorectal cancers [9,12,[31][32][33]. Chuma et al have found that HSP70 had the potential to be applied in the development of a sensitive marker to diagnose HCC in an early stage, from non-cancerous liver tissues to pre-cancerous lesion [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several SBP1 complex proteins are associated with malignant features of cancer cells (Table 1). HSP72 is expressed in primary and metastatic breast cancer tissue 21) and overexpression of HSP72 is correlated with poor prognosis in esophageal squamous cell carcinoma 22) . Engulfment and cell motility protein 1 (ELMO1) is aberrantly regulated in breast cancer chemotaxis and invasion 23) and highly expressed in rhabdomyosarcoma 24) and gliomas 25) .…”
Section: Discussionmentioning
confidence: 99%